THE DOCTORS AND THE STATE (1922): A RELATIONSHIP OF TENSION AND COLLABORATION. - André de Faria Pereira Neto (Clio: Revista de Pesquisa Histórica, 2006)
This article discusses the importance of the State in the professionalization process. He defends the idea that the state plays a central role both in the history of the successful professions and in the history of those who have passed away. Its object of analysis is the reciprocal relation of interests that was established between the elite of the medical profession and the Brazilian State, in the early twentieth century. In that context, the State increased its intervention in social life, in general, and in the professions, in particular. Decrees 11,530 / 1915 and 14,354 / 1920, for example, established criteria for the organization and official recognition of university institutions and planned a national medical service - measures with great potential to interfere in the medical labor market. This article accompanies the reactions of the medical elite, gathered in the National Congress of Practitioners (1922), to these legal prescriptions. He demonstrates that an influential and powerful part of the medical corporation, assembled at that event, held at least two professional projects inserted in a particular historical context, which in a way complement each other. One was to defend the expansion of state power to ensure the preservation of professional practice, in a liberal way, in Brazil in the early twentieth century. Another pleaded that the spheres of prestige and power that were being opened within the public power were occupied by doctors. Between this professional elite and the state a relationship of tension and collaboration was established. Tension, because the medical elite pressed the state to satisfy particular interests, considered as unresolved. Collaboration, since it aimed to act in high spheres of power, guaranteeing, with their knowledge, relationships and skills, the best possible governance in the execution of public health policies.